Social semiotic analysis and efforts to preserve the old mantra of Serdang Malay ethnomedicine in Serdang Bedagai regency, north Sumatra - Kartolo, Rahmat; Sutikno, Sutikno; Sutarini, Sutarini; Nirmawan, Nirmawan; Rosadi, Mimi; Juwita, Putri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research aims to document and analyze semiotic studies in Serdang Malay Ethnomedicine mantra texts, especially regarding signs and markers which are believed to have spiritual power in Kuala Lama Village, Serdang Bedagai Regency, North Sumatra. This research uses a qualitative approach with field data obtained through observation, in-depth interviews and documentation. The results of this research show that in the old Malay Serdang mantra, there are two main signs, namely the sound or phrase "Bismillahirrohmanirrohim" which always appears at the beginning or above the mantra sentence. The two words "Hu" have a social meaning as a place to express requests for desires, recognition of human helplessness, and special sentences in begging. The research conclusion shows that the semiotic social meaning of the old Malay Serdang mantra lies in the sound "Bismillahirrohmanirrohim," which is an expression of a request for healing to God. In the context of ethnomedicine treatment, the use of this mantra also reflects cooperation and mutual assistance between the Serdang Malay community.